Marginalna Evropa - Vogrinčič Čepič, Ana (Družboslovne razprave, 2009)
The article presents the findings of a media research analysis that examined newspaper coverage of EU-related topics (i.e. the European Union, intercultural dialogue and the Slovenian Presidency of the Council of the EU')in two Slovenian dailies, Delo and Dnevnik, between January and June 2008. It focuses on articles which only just mention but do not deal per se with EU issues and were therefore categorised as marginal. As such, they function as repositories of meanings, revealing latent conceptions of the common European space. These ephemeral references may indeed not be overtly significant, but they are also not necessarily meaningless or value-neutral. The author differentiates between the types of marginal remarks and demonstrates the effects of the ephemeral by applying critical discourse analysis to the selected examples. Quantitative analysis offers a thematic and genre-based comparison between substantial and marginal EU articles published in Delo and Dnevnik, revealing their distinct editorial politics. Among others, the findings confirm that, although ephemeral and insignificant, such remarks strengthen the everyday presence of the EU and thus represent a relevant contribution to the media image of the EU as a whole.
Keywords: European Union; Evropska unija; Mass media; Množični mediji; Newspapers; Časniki; Analiza vsebine; Content analysis; Slovenia; Slovenija; Delo (periodična publikacija); Dnevnik (periodična publikacija; informiranje; poročanje; analize